PEMBERIAN REBUSAN DAUN SIRIH MERAH EFEKTIF MENURUNKAN KADAR GULA DARAH PADA DIABETES MELLITUS - Ratnasari, Nita Yunianti; Nurshana, Rimbaini Budi (Jurnal AKPER GSH, 2019)
Diabetes comes from the Greek meaning "to drain or divert" (siphon). Mellitus comes from the Latin meaning sweet or honey. Diabetes Mellitus Disease (DM) can be interpreted as individuals who drain a large volume of urine with high glucose levels. Diabetes Mellitus (DM) is a disease characterized by an absolute presence of insulin or a relative decrease in cell insensitivity to insulin. DM can also be interpreted as a metabolic disorder characterized by hyperglycemia associated with abnormalities in the metabolism of carbohydrates, fats, and proteins caused by a decrease in insulin secretion or a decrease in insulin sensitivity or both leading to chronic complications of microvascular, macrovascular, and neuropathy.Â  Indonesia is the 7th country with 8.5 million DM sufferers after China, India, and the United States, Brazil, Russia, Mexico. Dm incidence rate according to Basic Health Research (RISKESDAS) in 2014, there was an increase from 1.1 % in 2007 increased to 2.1 % in 2013 from the overall population of 250 million people. Develop a resume of nursing care in patients with DM with the act of giving a decoction of red betel leaves to lower blood sugar levels. This study uses a case study method. Participants were 3 respondents. The instruments used are red betel leaves, glasses, hot water, and stationery. The majority of respondents said blood circulation was smooth. This is in accordance with the criteria of results that have been determined by researchers at the stage of nursing planning so that the problem of ineffectiveness of peripheral tissue perfusion can be resolved. A decoction of red betel leaf water is proven to overcome the ineffectiveness of peripheral tissue.